2019
DOI: 10.1002/bit.26897
|View full text |Cite
|
Sign up to set email alerts
|

Engineering self‐flocculating Halomonas campaniensis for wastewaterless open and continuous fermentation

Abstract: Halomonas has been developed as a platform for the next generation industrial biotechnology allowing open and nonsterile growth without microbial contamination under a high-salt concentration and alkali pH. To reduce downstream cost associated with continuous centrifugation and salt containing wastewater treatment, Halomonas campaniensis strain LS21 was engineered to become self-flocculating by knocking out an etf operon encoding two subunits of an electron transferring flavoprotein in the predicted electron t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 56 publications
(91 reference statements)
0
22
2
Order By: Relevance
“… 59 Ling et al reported that glucose-grown Halomonas campaniensis LS21 could accumulate 45% PHB, producing approximately 2.7 g/L PHB. 60 This PHB production is lower than those observed in this study when strain ZD1 was grown on crude glycerol or on high-strength saline wastewater. Additionally, these extremophiles require high salinity (150–200 g/L, i.e., 15–20% NaCl) in the growth medium, 59 which is considered to be the major bottleneck in their potential application for the industrial production of PHB.…”
Section: Resultscontrasting
confidence: 63%
“… 59 Ling et al reported that glucose-grown Halomonas campaniensis LS21 could accumulate 45% PHB, producing approximately 2.7 g/L PHB. 60 This PHB production is lower than those observed in this study when strain ZD1 was grown on crude glycerol or on high-strength saline wastewater. Additionally, these extremophiles require high salinity (150–200 g/L, i.e., 15–20% NaCl) in the growth medium, 59 which is considered to be the major bottleneck in their potential application for the industrial production of PHB.…”
Section: Resultscontrasting
confidence: 63%
“…Cell shape is also an important factor influencing further cell separation from the culture broth. A convenient downstream process has been designed in engineered Halomonas campaniensis LS21,by deleting an etf operon encoding two subunits of an electron transferring flavoprotein, causing self-flocculation and an easy and rapid recovery at the bottom of the bioreactor (Ling et al, 2019;Shen et al, 2019).…”
Section: Challenges and Perspectives For Effective Pha Exploitationmentioning
confidence: 99%
“…Thus, controlling cell morphology efficiently enhanced PHB accumulation in H. campaniensis LS21. Furthermore, a self-flocculating H. campaniensis strain LSKO was obtained by knocking out a nonessential etf operon encoding the α and β subunits of an electron transfer flavoprotein [139]. LSKO accumulated up to 45% (wt) PHB.…”
Section: Enhancement Of Pha Synthesismentioning
confidence: 99%